Degradation of sterols and terrigenous organic matter in waters of the Mackenzie Shelf, Canadian Arctic - Rontani, Jean-François; Charrìère, Bruno; SEMPERE, Richard; Doxaran, David; Vaultier, Frédéric; Vonk, Jorien E.; Volkman, John K. (Organic Geochemistry, 2014)
International audience Sterols and their biotic and abiotic degradation products were quantified in suspended particulate matter (SPM) from surface waters in the Mackenzie River mouth to the Beaufort Sea shelf (Canadian Arctic). 24-Ethylcholesterol (sitosterol) and 24-methylcholesterol (campesterol) appeared to be extensively degraded by bacterial and especially autoxidative degradation in the samples. Degradation was most extensive in some samples from the outer boundaries of the plume, which exhibited much higher sitosterol/campesterol ratio values than previously observed in studies of the Beaufort Sea. The lack of reactivity of specific planktonic sterols such as cholesterol, 24-methylcholesta-5,22E-dien-3β-ol (epi-brassicasterol) and 24-methylenecholesterol and the good correlation between the abundances of sitosterol, campesterol and dehydroabietic acid (DHAA, a biomarker of Pinaceae resin) oxidation products allowed us to attribute the main origin of these two sterols to terrigenous vascular plants. A good correlation was observed between the extent of autoxidation and salinity, suggesting that the free radical oxidation is enhanced via contact with seawater. Laboratory incubation of Mackenzie River SPM in Milli-Q water and seawater confirmed this proposal. To explain the specific induction of autoxidation on vascular plant-derived material, a mechanism involving homolytic cleavage of photochemically produced hydroperoxides resulting from the senescence of higher plants on land is proposed. Cleavage could be catalyzed by redox-active metal ions released from SPM in the mixing zone of riverine water and marine water. The greatest extent of degradation observed at outer boundaries of the plume is attributed to preferential settling of lithic material relative to less dense higher plant debris increasing the proportion of highly degraded vascular plant material in the SPM. The results are important for this ecologically vulnerable region, where destabilization of permafrost by global warming is expected to ...